Analisis Komunikasi Antar IoT Middleware Dengan Node Sensor Kamera Berbasis Raspberry Pi Zero - Yazid Yazid; Eko Sakti Pramukantoro; Ari Kusyanti (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Development of middleware that has been done in previous research which refers to interoperability problem. Interoperability issues are raised that refers to the development of middleware in order to connect devices that use different protocols namely CoAP, MQTT and Websocket protocol. Tests on the previous studies used DHT22 and nodemcu as sensors. The result was that node sensor and IoT can communicate well with delay parameters, packet loss and overhead of each protocol used. The previously developed IoT Middleware aside from the idea of ​​syntactical interoperability, is also developed with the aim of semantic interoperability, where semantic interoperability is the process of sending data that refers to the content and context of data sent. However, previous studies of middleware testing were limited to syntactical interoperability, where in this study semantic testing will be done, with data structures sent differently than usual and data sent in the form of images, animated moving images and video. Based on the test results, the middleware is able to receive the data, with the results. At the time of transmitting images with resolution 1360x768. The lowest obtained delay is in QoS 2 and the highest in QoS 0.002993 seconds. When transmitting images with 1024x768 resolution. The lowest obtained delay is in QoS 2 and the highest in QoS 0.003959 seconds. When transmitting images with 800x600 resolution. The lowest received delay is in QoS 2 and highest on QoS 0.006523 seconds.